THE EFFECT OF LEADERSHIP STYLES ON STAFF PERFORMANCE: A CASE STUDY OF REAL ESTATE COMPANIES IN PHNOM PENH, CAMBODIA - Khath, Bora; Tan, Saroeun (Srawung: Journal of Social Sciences and Humanities, 2024)
Leaders in the real estate business in Cambodia have challenges that require them to use their leadership style in leading staff to work with high performance. The main objectives of this research are to identify the effect of leadership style on employee performance through motivation; to assess the effectiveness of leadership style and its effect on employee performance through motivation; to analyze the effect of leadership style on employee performance through motivation; to provide conclusions and implications about the effect of leadership style on employee performance through motivation; and to provide conclusions and implications about the effect of leadership style on employee performance through motivation in the real estate sector in Phnom Penh, Cambodia. The researcher selected 317 respondents to survey in eight real estate agency companies in Phnom Penh, Cambodia. In addition, key informants from middle and upper management were selected for semi-structured interview questions through purposive sampling technique. The research findings indicated that all five leadership styles including Transformational, Transactional, Democratic, Bureaucratic and Servant leadership styles are more effective towards employee motivation for private companies in the real estate sector in Phnom Penh, Cambodia. Transformational, Democratic and Servant leadership styles are more effective styles on employee performance for private companies in the real estate sector in Phnom Penh, Cambodia. While Transactional and Bureaucratic have no impact on employee performance for private companies in the real estate sector in Phnom Penh, Cambodia.